Pengaruh Lingkungan Kerja, Motivasi Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan - Pramiswari, Galih Intan; Sunaryo, Hadi; Rahman, Fahrurrozi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract The study seeks to investigate the impact of the workplace environment, motivation, and adherence to work discipline on the performance of employees (at the Batu City Regional Financial and Asset Agency Office). This type research employs a quantitative approach. approach and the data collection method used in this research is questionnaire data. In this research, the sample used was 48 employees who would be used as research objects. The analytical method used in this research is multiple linear analysis with hypothesis testing using the F test and t test. Based on the results of this research, it shows that the work environment, work motivation and work discipline simultaneously influence employee performance, while partially the work environment influences employee performance, work motivation influences employee performance and work discipline influences employee performance Keywords: Work Environment, Motivation, Discipline And Employee Performance